تقييم دقة بعض الطرق التقريبية المستخدمة في تحديد منحني مقاومة الجر لأبدان بعض السفن، عن طريق المقارنة بنتائج برنامج Delftship (Latakia University Journal -Engineering Sciences Series, 2019)
يُعالج البحث واحدة من القضايا الهامة الخاصة بمراكز الأبحاث البحرية، وترسانات بناء السفن المتعلقة بالتحديد الأمثل من حيث الدقة لمنحني مقاومة الجر لبدن السفينة كتابع لسرعة إبحارها في ظروف الاستثمار الحقيقية. يتضمن هذا البحث تقييم دقة منحنيات الطرق التقريبية المستخدمة عن طريق إجراء مقارنة تحليلية إحصائية بين منحنيات الطرق التقريبية مع مكافئاتها ومنحنيات طريقة Delft Series الخاصة ببرنامج Delftship المعتمد عالمياً من قبل العديد من المراكز البحثية، والأكاديميات البحرية، وذلك من خلال تحديد المعدل العام الوسطي لمعامل شدة الارتباط، وتحديد أيضاً المعدل العام الوسطي للانحراف النسبي الوسطي المئوي للمقاومات المحددة، وفق الطرق المعتبرة بالمقارنة مع المقاومات المحددة وفق طريقة Delft Series ، من أجل عدة سفن مدروسة، عند حالات عديدة تحميل محتملة، ضمن مجالات محددة للسرعة. أظهرت النتائج أن مقدار التباين (من حيث قيم و قيم ) لمنحنيات الطرق الأنسب أو الأقرب إلى منحنيات طريقة Delft Series يقع ضمن مجال مقدار الإضافة الملاحية (الزيادة في مقدار المقاومة) المتعلقة بعوامل عشوائية تخص الظروف المناخية  المسيطرة على الخطوط الملاحية التي تعمل عليها السفينة. This research deals with one of the important issues related to the maritime research centers and shipyards which are related to the optimal specification concerning the accuracy of specifying the curve of hull resistance of the ship body in accordance with its speed during the actual investment conditions. The research includes an evaluation of the accuracy extent of the already used curves of the approximating methods.   This evaluation is done by conducting an analytical and calculating comparison between the curves of the approximating methods and their equivalence on the one hand and the curves of Delft Series method, on the other. The latter is exclusive of Delftship program which is approved of internationally by a few research centers and maritime academies.   The comparison is done by specifying the general medial average of  the coefficient correlation, in addition to the specification of the general medial average of the relative medial inclination of the specified resistance according to the considered methods in contrast to the resistances appointed by Delft  Series methods. All these procedures are applied on several studied ships during a few situations of potential loading cases on  speed fields. The research conclusions reveal that the value of difference (the values of r and the values of (∆R/R %)) of the most appropriate method curves or those which are closest to Delft Series curve method is within the scope of the value of maritime addition (an increase in the value of resistance) which is connected with random factors related to the climate conditions that control maritime lines on which these ships are invested.